Feminist Cyberactivism in Chile. the Experience of the Observatory Against Street Harassment [Ciberactivismo Feminista en Chile. la Experiencia del Observatorio Contra el Acoso Callejero] - Jara-Reyes, R (Universidad del Pacífico Press, 2022)
This article addresses the issue of feminist cyberactivism, focusing on the experience of the Observatory against Street Harassment (OCAC in Spanish) in Chile, between 2014 and 2017. Based on an analysis centred on its digital strategy, the article explores its effects on three areas: the organi-zation of the collective, identity and their ability to put the issue of gender violence on the public agenda, by promoting a bill proposal named “Respeto Callejero” (Spanish for “Respect in the Streets”). Three study techniques were used: interviews with movement participants, analysis of Facebook metrics and keywords analysis in traditional and digital media. Amongst the results, we can point out that before the emergence of this organization there was no media coverage in Chile regarding Street Harassment, and, therefore, the digital strategy of positioning and call to action developed by the OCAC has allowed for a gradual change in these affairs, installing the matter of gender violence in public spaces. © BELÉN MERINO SOLAR et al.